2019
DOI: 10.1111/papr.12814
|View full text |Cite
|
Sign up to set email alerts
|

Medication Use and Pain Management in Pregnancy: A Critical Review

Abstract: Background Pain during pregnancy is common, and its management is complex. Certain analgesics may increase the risk for adverse fetal and pregnancy outcomes, while poorly managed pain can result in adverse maternal outcomes such as depression and hypertension. Guidelines to assist clinicians in assessing risks and benefits of exposure to analgesics for the mother and unborn infant are lacking, necessitating evidence‐based recommendations for managing pain in pregnancy. Methods A comprehensive literature search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 159 publications
2
67
0
6
Order By: Relevance
“…Acetaminophen is the most common analgesic used in pregnancy, and in general is considered 'low risk' to the pregnancy and fetus. 45 However, these data add to other emerging data suggesting an associated between acetaminophen exposure and adverse birth outcomes. For example, in a cohort of 1200 patients in Ontario, selfreported acetaminophen use was associated with small for gestational age and low birthweight.…”
Section: Discussionsupporting
confidence: 51%
“…Acetaminophen is the most common analgesic used in pregnancy, and in general is considered 'low risk' to the pregnancy and fetus. 45 However, these data add to other emerging data suggesting an associated between acetaminophen exposure and adverse birth outcomes. For example, in a cohort of 1200 patients in Ontario, selfreported acetaminophen use was associated with small for gestational age and low birthweight.…”
Section: Discussionsupporting
confidence: 51%
“…We observed that, over 1.5 years since the first-in-class erenumab was authorised by the FDA, no specific maternal toxicities, patterns of major birth defects, or spontaneous abortion have emerged as hallmarks of toxicity with erenumab, galcanezumab and fremanezumab. Because of ethical restrictions on the inclusion of pregnant women in randomised clinical trials, the majority of information on drug safety in pregnancy and lactation either derives from observational studies in the post-marketing setting or relies on experts' opinions (25). Expert-based guidelines from the European Headache Federation suggest avoiding the use of monoclonal antibodies acting on the CGRP system for migraine prevention in pregnant or nursing women (26).…”
Section: Discussionmentioning
confidence: 99%
“…The GP may still recommend using an NSAID regime such as that outlined for moderate dental pain, as NSAIDs are not absolutely contraindicated until 30 weeks' gestation and beyond. 14 Patients who are breastfeeding can be given NSAIDs, but the higher doses should only be used in exceptional circumstances and after discussion with the GP. Paracetamol is preferred.…”
Section: Pregnancymentioning
confidence: 99%